THE CHOICE OF THE METHOD OF TREATMENT OF ABDOMINAL ABSCESSES IN ADULT PATIENTS - Bababeyli, E.Yu. (World of Medicine and Biology, 2023)
The results of a comparative study of 326 patients who underwent various types of surgical treatment of abdominal abscesses in 2014–2022 were evaluated. Abdominal abscesses develop after various kinds of inflammatory pathologies, especially peritonitis. 178 patients (54.6 %) in the main group were treated with invasive methods, and 148 patients (45.4 %) in the control group were treated with open methods. The results in both groups were investigated. In the main group, the indicators of recovery time increased by 1.9±1.2 times, and complications, relapses and mortality decreased by 1.7±0.8 times, 1.2±0.6 times and 1.1±0.4 times, respectively. The results of invasive methods, compared with open methods, are relatively simple, easy, financially cheap, convenient for patients and more effective. Treatment consists in drainage, surgical or percutaneous, the effectiveness of percutaneous drainage of abdominal abscesses reaches 74–96.4 %
Keywords: abdominal abscess; laparoscopy; aspiration-puncture under CT and ultrasound control; biopsy; drainage; catheterization